Heat and mass transfer of Ag-〖Fe〗_3 O_4/H_2 O Hybrid Nanofluid flow over a nonlinear Stretching Sheet. - C. Sulochana , T. Prasanna Kumar (International Journal of Advanced Science and Technology, 2020)
Magnetohydrodynamic boundary layer flow of hybrid nanofluid flow over a nonlinear stretching surface is investigated with thermal radiation and viscous dissipation effects. Similarity variable approach is used to transform partial differential equations into system of ordinary differential equations and solved numerically with the help of shooting technique. Silver ,iron oxide nanoparticle are suspended into base fluid water in order to analyze the thermal behavior of the fluid flow. The influence of various flow parameters such as magnetic field strength (M),thermal radiation (R),Eckert number(Ec),thermoporosis parameter(Nt) and Brownian motion(Nb) on velocity ,temperature and nano particle volume fraction profiles are presented in table and graphs format. We observed that nonlinear parameter (n) ,radiation parameter(R), thermoporosis parameter(Nt), Brownian motion(Nb) enhances temperature profile and this increment is more in case of hybrid nanofluid as compared to mono particle nanofluid.